Targeted deletion of NFAT-Interacting-Protein-(NIP) 45 resolves experimental asthma by inhibiting Innate Lymphoid Cells group 2 (ILC2) - Koch, Sonja; Knipfer, Lisa; Kölle, Julia; Mirzakhani, Hooman; Graser, Anna; Zimmermann, Theodor; Kiefer, Alexander; Melichar, Volker O.; Rascher, Wolfgang; Papadopoulos, Nikolaos G.; Rieker, Ralf; Raby, Benjamin A.; et al. (Scientific Reports, 2019)
Here we investigated the role of NFAT-interacting protein (NIP)-45, an Interleukin (IL)-4 inducing Transcription Factor, and its impact on the differentiation of Group 2 Innate -Lymphoid -Cells (ILC2s) in the pathogenesis of asthma. NIP45, a transcription factor regulating NFATc1 activity, mRNA was found to be induced in the Peripheral Blood mononuclear cells (PMBCs) of asthmatic pre-school children with allergies and in the peripheral blood CD4+ T cells from adult asthmatic patients. In PBMCs of asthmatic and control children, NIP45 mRNA directly correlated with NFATc1 but not with T-bet. Targeted deletion of NIP45 in mice resulted in a protective phenotype in experimental asthma with reduced airway mucus production, airway hyperresponsiveness and eosinophils. This phenotype was reversed by intranasal delivery of recombinant r-IL-33. Consistently, ILC2s and not GATA3+ CD4+ T-cells were decreased in the lungs of asthmatic NIP45−/− mice. Reduced cell number spleen ILC2s could be differentiated from NIP45−/− as compared to wild-type mice after in vivo injection of a microcircle-DNA vector expressing IL-25 and decreased cytokines and ILC2 markers in ILC2 differentiated from the bone marrow of NIP45−/− mice. NIP45 thus emerges as a new therapeutic target for the resolution of the airway pathology, down-regulation of ILC2s and mucus production in asthma.
CRIS-Team Scopus Importer:2019-11-08